Patient Loyalty in the HospitalPatient Relationship: The MediatingRole of Social Media - (:unkn) unknown (My University, 2019)
This study aimed to investigate role of social media on patient loyalty. Based onrelated literature review, for assessing patient loyalty, a measurement scale, testingsatisfaction shared by patient through social media, patient trust, strength ofhospital-patient communication on social media, and perceived image of hospitalon social media was developed. The data was collected from 625 patients by selfadministered online questionnaires. Hypotheses about the role of social mediawere suggested based on existing body of knowledge so that we aimed to examineunderlying mechanism between the predictors and patient loyalty by means ofStructural Equation Modelling (SEM) framework. Findings demonstrated thatsatisfaction, shared by patients through social media, mediated the associationbetween patient trust, strength of hospital-patient communication on social media,perceived image of hospital on social media, and patient loyalty. The findingsprovide an original empirical model with respect to gaining loyal patients whomare customers of hospitals and highlight the important role of social media in healthcommunication.

Bu çalışma, sosyal medyanın hasta sadakati üzerindeki rolünü incelemeyi hedeflemiştir. Hasta sadakatini değerlendirmek için; hastalar tarafından sosyal medyada paylaşılan memnuniyeti, hasta güvenini, sosyal medya üzerinde hastanehasta iletişiminin gücünü ve hastanenin sosyal medyada algılanan imajını test eden bir ölçüm envanteri, ilgili literatür temel alınarak geliştirilmiştir. Veriler çevrimiçi anket vasıtasıyla 625 kişiden toplanmıştır. Literatürde yer alan bulgular göz önünde bulundurularak hipotezler geliştirilmiş ve hasta sadakatini yordayan değişkenlerin Yapısal Eşitlik Modeli (YEM) aracılığı ile incelenmesi amaçlanmıştır. Çalışmanın sonuçları, sosyal medyada hastalar tarafından paylaşılan memnuniyetin; yordayıcı değişkenler (hasta güveni, sosyal medya üzerinde hastane-hasta iletişiminin gücü, hastanenin sosyal medyada algılanan imajı) ve hasta sadakati arasındaki ilişki üzerinde aracı değişken olduğunu göstermiştir. Bulgular, hastanelerin müşterileri olan sadık hastalar kazanma noktasında özgün ampirik bir model sağlamakla beraber sosyal medyanın sağlık iletişimindeki önemini vurgulamaktadır.
Hastane-Hasta İlişkisi Bağlamında Hasta Sadakati: Sosyal Medyanın Aracı Rolü